2021
DOI: 10.1093/molbev/msab220
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Renal-Disease Factor APOL1 Results in Cis and Trans Orientations at the Endoplasmic Reticulum That Both Show Cytotoxic Effects

Abstract: The recent and exclusively in humans and a few other higher primates expressed APOL1 (Apolipoprotein L1) gene is linked to African human trypanosomiasis (also known as African sleeping sickness) as well as to different forms of kidney diseases. Whereas APOL1’s role as a trypanolytic factor is well established, pathobiological mechanisms explaining its cytotoxicity in renal cells remain unclear. In this study, we compared the APOL family members using a combination of evolutionary studies and cell biological ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 95 publications
2
14
0
Order By: Relevance
“…and Wakashin et al. ( Muller et al., 2021 ; Wakashin et al., 2020 ), or possibly the GFP-APOL1 construct used compared to our artificial ΔMSALFL APOL1, that might be more toxic to cells. Notably, we used the African background (E150, I228, K255) in all constructs, therefore the attenuated ΔMSALFL APOL1 toxicity cannot be explained by a different APOL1 haplotype ( Lannon et al., 2019 ).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…and Wakashin et al. ( Muller et al., 2021 ; Wakashin et al., 2020 ), or possibly the GFP-APOL1 construct used compared to our artificial ΔMSALFL APOL1, that might be more toxic to cells. Notably, we used the African background (E150, I228, K255) in all constructs, therefore the attenuated ΔMSALFL APOL1 toxicity cannot be explained by a different APOL1 haplotype ( Lannon et al., 2019 ).…”
Section: Discussionmentioning
confidence: 81%
“…These conflicting finding can be reconciled by considering that some studies have used APOL1 constructs that lack signal peptide and showed that the signal peptide was dispensable for APOL1 cellular toxicity ( Granado et al., 2017 ; Lan et al., 2015a ; Nichols et al., 2015 ; Thomson et al., 2014 ), while other studies used APOL1 constructs that harbored non-cleavable signal peptide ( Khatua et al., 2015 ). Granado et al., and recently Muller et al., used GFP- APOL1 constructs that lack the signal peptide and were still expressed in the ER while retaining the toxicity potential ( Granado et al., 2017 ; Muller et al., 2021 ). Muller et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Zee et al showed that glomerular APOL1 expression or APOL1 risk alleles are associated with cellular/tissue changes in patients with FSGS [ 195 , 196 ]. ApoL2 is found mainly in the brain [ 197 ], but its function remains unknown in the kidneys. ApoL3 and ApoL4 are associated with cholesterol and sphingolipid transport/recycling to the plasma membrane in the lungs and other tissues [ 190 ], but their functions are also unknown in the kidneys.…”
Section: Roles and Biological And Pathological Functions Of Apolipopr...mentioning
confidence: 99%
“…We also analyzed the classical abalone sperm lysin sequence dataset that contains verifiable amino acid sites under positive and purifying selection [ 17 ]. The last example refers to an apolipoprotein family (APOL) that recently was investigated for adaptive evolution [ 18 ].…”
Section: Introductionmentioning
confidence: 99%